تأثير الإعلان عبر مواقع التواصل الاجتماعي في رضا المستهلك على لعلامة التجارية دراسة مسحية على عملاء شركة سيرياتيل في محافظة اللاذقية - نصور, ريزان; حماد, محمد (Latakia University Journal - Economic and Legal Sciences Series, 2018)
This study aimed to identify the ad through social networking sites and its importance and the definition of the concept of customer satisfaction to the brand, also aims to analyze the impact of advertising on social networking sites and customer satisfaction of the brand. In order to achieve this, the researcher identified and studied the impact of advertising through social media sites on the satisfaction of the customer to the brand, by conducting a survey of the customers of Syriatel in Lattakia. The study community included all the clients of Syriatel in Lattakia Governorate. The standard error of the percentage is 95% confidence interval. In the case of 50% of the population of the study in which the given property is available, and back to the statistical tables, the sample size is 384. The researcher distributed 463 questionnaires. Nostalgia 424 valid for study. The researcher concluded that there is a significant statistical effect between the (forms - characteristics - goals) advertising through social networking sites on the customer satisfaction of the brand. Through this study, the researcher presented a set of proposals and recommendations that are expected to help brand owners to enhance customer satisfaction with their brand and build positive attitudes towards them through social networking sites. هدفت هذه الدراسة إلى التعرف على دور الإعلان عبر مواقع التواصل الاجتماعي وأهميته والتعريف بمفهوم رضا العميل عن العلامة التجارية، كما تهدف إلى تحليل تأثير الإعلان عبر مواقع التواصل الاجتماعي على رضا العميل للعلامة التجارية. ولتحقيق ذلك قام الباحث بتحديد ودراسة تأثير الإعلان عبر مواقع التواصل الاجتماعي على رضا العميل عن العلامة التجارية، وذلك من خلال إجراء دراسة مسحية على عملاء شركة سيرياتيل في محافظة اللاذقية، وتضمن مجتمع الدراسة على جميع عملاء شركة سيرياتيل في محافظة اللاذقية ،وتم اختيار عينة الدراسة استناداً إلى معادلة الخطأ المعياري للنسبة المئوية وذلك عن معامل ثقة 95% وفي حالة أن نسبة مفردات مجتمع الدراسة التي تتوافر فيها الخاصية محل القياس =50% ،وبالعودة إلى الجداول الإحصائية تبين أن حجم العينة المناسب = 384 مفردة وقام الباحث بتوزيع 463استبيان تم استرداد 436 استبيان منهم 424 صالحة للدراسة. وتوصّل الباحث إلى وجود تأثير ذو دلالة إحصائية بين (أشكال-خصائص-أهداف) الإعلان عبر مواقع التواصل الاجتماعي على رضا العميل للعلامة التجارية. كما قدّم الباحث من خلال هذه الدراسة مجموعة من المقترحات والتوصيات التي من المتوقع أن تساعد أصحاب العلامات التجارية على تعزيز رضا العملاء عن علامتهم التجارية وبناء اتجاهات إيجابية نحوها عبر مواقع التواصل الاجتماعي.